Pemasangan Panel Solar untuk Penerangan Lampu Petani Serai Wangi di Desa Siabu, Salo, Kampar - Azriyenni; Amir Hamzah; Fri Murdiya; Suwitno; Pedia Aldy (Universitas Lancang Kuning, 2021)
Lack of electricity in the rural areas is quite limited to farmers in the lemongrass plantation in Siabu, Salo, Kampar. Their problem provides an idea to assemble solar panels for lighting supplies for lemongrass farmers. The method used for this activity is; field survey, assembly, calibration, and testing. In the test of the battery charging process has been carried out. Batteries charging are utilized 20 Ah and 60 Ah. The solar panels used are 2*50 Wp, Solar Charger Controller, battery, and inverter. The battery of 20 Ah load test results has an electricity of 30 Watt. The maximum battery voltage measured at 12.8 Volt with a load duration of 4 hours. The loading test is also carried out for a battery of 60 Ah has the same load that is a 30 Watt. In this test, the voltage is measured 12.8 Volt, a duration of electricity use for 11 hours.